Data chain management for planning in city logistics. (30th October 2009) - Ehmke, Jan Fabian; Meisel, Stephan; Engelmann, Stefan; Mattfeld, Dirk Christian
This contribution is about data chain management enabling route planning in city logistics. The transformation of raw data into reliable decisions requires effective data chain management. The data chain closes the gap between empirical collection of raw traffic data and decision-making in terms of route planning. We define the data chain for the support of route planning in city logistics. The data chain transforms raw empirical traffic data into planning data by first and second level aggregation. The single elements of the data chain are investigated in detail. We discuss basic issues of telematics-based data collection, data cleaning and data integration. The key element of the data chain is the aggregation by cluster analysis. Aggregated data is evaluated by explorative data analysis. Finally, the efficient application of aggregated data for route planning is illustrated.